Comparison of Triiodothyronine (T3), Tetraiodothyronine (T4), Freethyoxine (FT4), Thyroid Stimulating Hormone (TSH) Levels in with Liver Cirrhosis Patients Based on Child-Pugh Score at H. Adam Malik Central General Hospital, Medan - Beby Dewi Sartika; Leonardo Basa Dairi; Gontar Alamsyah Siregar (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2018)
Background: The liver is involved in thyroid hormone conjugation and excretion, as well as the synthesis of thyroid binding globulin. T4 and T3 regulate the basal metabolic rate of all cells.Method: The sample of this research was collected crosssectionally on 40 patients with liver cirrhosis based Child-Pugh score. Ultrasonography and Triiodothyronine (T3), Tetraiodothyronine (T4), Freethyoxine (FT4), thyroid stimulating hormone (TSH) levels examinations to know the difference between liver cirrhosis patients with Child-Pugh A, B, and C with ELISA method.Results: Statistical analysis showed there are not found significant differences in T3, T4, FT4, TSH levels in patients with of the liver cirrhosis based on the Child-Pugh score.Conclusion: Not found significant differences in thyroid hormone levels among patients with liver cirrhosis Child-Pugh A, B, and C.